Distinguishing Pure Honey from Honey Adulterated with Added Sugar Using the LC–MS/MS Method - La Ode Sumarlin; Etyn Yunita; Agustina Senjayani; Vetty Megantari (Jurnal Kimia Valensi, 2026)
Honey adulteration through the addition of sugar such as liquid sugar, cane sugar, fructose, and glucose remains a major concern affecting honey quality and authenticity. This study aimed to differentiate pure honey, sugar-adulterated honey, and synthetic honey using a liquid chromatography tandem mass spectrometry (LC-MS/MS) fingerprinting approach. Samples included pure acacia (A), longan (K), and kapok/randu (N) honeys, their corresponding sugar-adulterated variants, and synthetic honey (S) as a negative control. The results demonstrated that LC-MS/MS fingerprints effectively distinguished pure honey from adulterated and synthetic samples. Pure honeys exhibited more complex and specific metabolite profiles, whereas sugar addition led to simplified chromatographic patterns dominated by sugar-related compounds. Fructose- and glucose-adulteration produced metabolite profiles most similar to synthetic honey, with randu honey showing the highest sensitivity to fructose addition. Fructosylated compounds such as N-(1-deoxy-1-fructosyl)phenylalanine (Fru-Phe) and isomaltol were identified as indicators of sugar addition and thermal processing. In contrast, biologically and botanically derived metabolites, including umbelliferone, indoleacrylic acid, hypoxanthine, O-glutarylcarnitine, cyclic melatonin, phenethyl tiglate, and indole-3-carboxaldehyde, reflected nectar origin and natural biological processes. The detection of phenanthrene-3,4-diol further indicated environmental influences on honey composition. Overall, integrating processing indicators with biological and botanical markers provides a comprehensive and reliable framework for honey authentication via LC-MS/MS fingerprinting.